K+ channels and cell cycle progression in tumor cells - OUADID-AHIDOUCH, HALIMA; AHIDOUCH, Ahmed (Frontiers in Physiology, 2013)
K+ ions play a major role in many cellular processes. The deregulation of K+ signaling is associated with a variety of diseases such as hypertension, atherosclerosis, or diabetes. K+ ions are important for setting the membrane potential, the driving force for Ca2+ influx, and regulate volume of growing cells. Moreover, it is increasingly recognized that K+ channels control cell proliferation through a novel signaling mechanisms triggered and modulated independently of ion fluxes. In cancer, aberrant expression, regulation and/or sublocalization of K+ channels can alter the downstream signals that converge on the cell cycle machinery. Various K+ channels are involved in cell cycle progression and are needed only at particular stages of the cell cycle. Consistent with this idea, the expression of Eag1 and HERG channels fluctuate along the cell cycle. Despite of acquired knowledge, our understanding of K+ channels functioning in cancer cells requires further studies. These include identifying the molecular mechanisms controling the cell cycle machinery. By understanding how K+ channels regulate cell cycle progression in cancer cells, we will gain insights into how cancer cells subvert the need for K+ signal and its downstream targets to proliferate.